Nipsoft AB - Huber, Stefan; Solberg Søilen, Klaus (Jönköping International Business School, Jönköping, Sweden, 2004)
A large part of graduate engineers are hired directly by corpora- tions when they graduate from university. They typically spend most of their working life being employed. Only a few take the step into entrepreneurship and start their own business. One reason of this may be that university edu- cated engineers are not properly trained to run a business of their own. Many emphasize their short term personal economic situation even though they have developed a competitive business idea while in school.The founder and owner of recently started IT-firm Nipsoft AB, lo- cated in Sollefteå/Northern Sweden, tells the story of an exceptional career: Being an academically trained technician, he thought he might have to wait a long time before leading a corporation of his own. Under rather coinciden- tal circumstances he was able to start his own business at the age of 29. Af- ter a short time of struggle, he now leads his data system developing com- pany successfully. He believes that much of his achievements is due to the short economic education which he received in an independent organization. For students to start to think about the possibility of starting up companies they need to be taught how. krAft project, Case ID-010 krAft